2015
DOI: 10.1017/s2040174415000136
|View full text |Cite|
|
Sign up to set email alerts
|

Regional differences in birth size: a comparison between the Helsinki Birth Cohort Study and contemporaneous births on the Åland Islands

Abstract: The Åland Islands were recently ranked as Finland's healthiest region with lower prevalence of several non-communicable diseases compared with the national mean. We have compared birth characteristics of 1697 individuals born on the Åland Islands between 1937 and 1944 with contemporaneous data from the Helsinki Birth Cohort Study (HBCS; n=11,808). This is a first step towards a potential future analysis of Ålandic health from a life-course perspective. Mean birth weight and length were calculated for both coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…When BWs from Åland, described as Finland's healthiest region, were compared with BWs from Helsinki in the 1930s, mean BWs from Åland was shown to be higher. 5 It has been suggested that a high intake of omega-3 fatty acid, from dietary fish consumption, is associated with a longer gestational time period and thereby a somewhat higher BW. 23,24 Since Åland is an archipelago located by the sea, its population can be assumed to have had a high consumption of fish during historical times and even at present, also involving the diet of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When BWs from Åland, described as Finland's healthiest region, were compared with BWs from Helsinki in the 1930s, mean BWs from Åland was shown to be higher. 5 It has been suggested that a high intake of omega-3 fatty acid, from dietary fish consumption, is associated with a longer gestational time period and thereby a somewhat higher BW. 23,24 Since Åland is an archipelago located by the sea, its population can be assumed to have had a high consumption of fish during historical times and even at present, also involving the diet of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Some historical examples have been used to link a higher mean BW, as well as adult tallness, with better health conditions and increased longevity on the population level, for example in Åland, a Swedish-speaking archipelago province of western Finland. [3][4][5] Halland is a county located in south-west Sweden with 325,000 inhabitants. For more than a century it has been known that this population enjoys the highest mean life expectancy in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…64,65 Furthermore, babies born to obese mothers have a compromised immune system. 66 The Helsinki Birth Cohort comprises 13,345 men and women born during 1934-1944, 67,68 and an older cohort comprising 7086 people born during 1924-1933. 69 The Helsinki Birth Cohort is a gold mine for placentologists because at the time of birth, midwives and nurses measured the weights, widths and lengths of all births in Helsinki hospitals during those periods of time.…”
Section: Placental Lessons From the Helsinki Birth Cohortmentioning
confidence: 99%
“…The Helsinki Birth Cohort comprises 13,345 men and women born during 1934–1944, 67,68 and an older cohort comprising 7086 people born during 1924–1933. 69 The Helsinki Birth Cohort is a gold mine for placentologists because at the time of birth, midwives and nurses measured the weights, widths and lengths of all births in Helsinki hospitals during those periods of time.…”
Section: Placental Lessons From the Helsinki Birth Cohortmentioning
confidence: 99%